2022
DOI: 10.1001/jamainternmed.2022.3938
|View full text |Cite
|
Sign up to set email alerts
|

Price Comparison of Human and Veterinary Formulations of Common Medications

Abstract: In 2021, the US Food and Drug Administration oversaw the marketing of approximately 20 000 medications for human use and 1600 for veterinary use. Some medications are common to both pets and humans, and price differences can be extreme. In 1991, levamisoleintroduced in the 1960s as a veterinary antiparasitic medication-demonstrated efficacy in treating human colon cancer. The introductory human price of Janssen's Ergamisol (brand-name levamisole; $5 per 50-mg tablet) was 100 times the then veterinary price (ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…13 In a recent cross-sectional study, researchers found that prices for two-thirds of human medications were higher compared to pets. 14 Therefore, it is important to regulate veterinary drugs to not only avoid inadvertent administration to humans but also to curtail drug abuse.…”
Section: Discussionmentioning
confidence: 99%
“…13 In a recent cross-sectional study, researchers found that prices for two-thirds of human medications were higher compared to pets. 14 Therefore, it is important to regulate veterinary drugs to not only avoid inadvertent administration to humans but also to curtail drug abuse.…”
Section: Discussionmentioning
confidence: 99%
“…The inexplicable cost differences between pet and human versions of the same generic drug raise a broader question: how much longer will the mismatch between the aspirational mission of improving health, and the strategic goal of pricing drugs to maximize profits, be acceptable in the US? Drug companies are routinely contacted by patients who are unable to afford their medications .…”
Section: Lobbying Against Reforms To Reduce Drug Pricesmentioning
confidence: 99%
“…As a result, millions of people are unable to afford important, often lifesaving medicines. In this issue of JAMA Internal Medicine , Haque et al demonstrate the higher prices for humans than for pets in the US for the same generic drug. Their study raises a fundamental question: how large a margin between production costs (including the costs of research and manufacturing) and sales price is acceptable for prescription drugs?…”
mentioning
confidence: 99%
“…It is well known that drug prices in the US are greater than those in many other countries . In this issue of JAMA Internal Medicine , Haque and colleagues report that within the US, prices for human formulations of drugs generally exceed that of veterinary formulations. The authors raise the important issue of price discrimination in the prescription drug market, meaning that consumers are charged different prices for essentially the same product.…”
mentioning
confidence: 99%
“…We have long known that markets for prescription drugs are, by design, not competitive, and the burden of financing innovation has disproportionately fallen on individuals in the US. Many have argued that we should not pay more than other countries for drugs, and Haque and colleagues suggest that we should not pay more than our pets (and farm animals). Although distributional concerns may motivate a substantive amount of policy interest, the core focus should balance innovation incentives and spending.…”
mentioning
confidence: 99%